Multisensory cues capture spatial attention regardless of perceptual load. - Santangelo, V; Spence, C (2007)
We compared the ability of auditory, visual, and audiovisual (bimodal) exogenous cues to capture visuo-spatial attention under conditions of no load versus high perceptual load. Participants had to discriminate the elevation (up vs. down) of visual targets preceded by either unimodal or bimodal cues under conditions of high perceptual load (in which they had to monitor a rapidly presented central stream of visual letters for occasionally presented target digits) or no perceptual load (in which the central stream was replaced by a fixation point). The results of 3 experiments showed that all 3 cues captured visuo-spatial attention in the no-load condition. By contrast, only the bimodal cues captured visuo-spatial attention in the high-load condition, indicating for the first time that multisensory integration can play a key role in disengaging spatial attention from a concurrent perceptually demanding stimulus.